Profile of acute coronary syndrome in young diabetics: a review - Narayanan, Lakshmi; Hanifah, Mohamed (International Journal of Advances in Medicine, 2020)
The clinical presentation and angiographic findings of coronary artery disease (CAD) varies from diabetic and non-diabetic patients and varies with the age of presentation. Coronary artery disease in patients below the age of 45 is a special subset. The objective of this study is to compare the clinical and angiographic profile in patients with the acute coronary syndrome (ACS) with diabetes mellitus (DM) and without DM below the age of 45 years. Clinical Presentation of coronary artery disease in young patients with various risk factors differs, which plays an important role in management strategies. This was conducted through internet search on PubMed and ProQuest database from 2000 to until 2019. Key words used for searching are acute coronary syndrome, young diabetics, and clinical, angiographic profile. An important exclusion criterion is studies which included type one diabetic patients. Totally 35 papers were reviewed. Pattern of involvement of coronary arteries as assessed by the coronary angiographic study is found to be different in younger CAD patients. Atypical clinical presentation and distinct angiographic finding are common in diabetics below the age of 45. In most of the studies single vessel disease (SVD) is the most common angiographic finding in young CAD and non-diabetics. While the diabetics showed the more diffuse pattern of double vessel disease (DVD).